2016
DOI: 10.1016/j.rmb.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Valoración de metabolitos de testosterona, progesterona y estrógeno en excretas de venado cola blanca (Odocoileus virginianus) como método para determinar el sexo

Abstract: Valoración de metabolitos de testosterona, progesterona y estrógeno en excretas de venado cola blanca (Odocoileus virginianus) como método para determinar el sexo Measurement of fecal testosterone, progesterone and estrogen metabolites as a method to determine sex in white tailed deer (Odocoileus virginianus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
2
1
1
Order By: Relevance
“…The values of cortisol and testosterone levels in this study were low, even though inside the ranges reported in various studies performed in white-tailed deer and other deer species (Pelletier et al, 2003;Chunwang et al, 2004;McCoy & Ditchkoff, 2012;López & Montes, 2016). This could have occurred by the microbial activity in feces that metabolizes steroid hormones to metabolites, with which there were no crossed reaction with antibodies used in this study.…”
Section: Season Umacontrasting
confidence: 44%
See 1 more Smart Citation
“…The values of cortisol and testosterone levels in this study were low, even though inside the ranges reported in various studies performed in white-tailed deer and other deer species (Pelletier et al, 2003;Chunwang et al, 2004;McCoy & Ditchkoff, 2012;López & Montes, 2016). This could have occurred by the microbial activity in feces that metabolizes steroid hormones to metabolites, with which there were no crossed reaction with antibodies used in this study.…”
Section: Season Umacontrasting
confidence: 44%
“…Los valores de los niveles de cortisol y testosterona en este estudio fueron bajos, aunque dentro de los rangos reportados en varios estudios realizados en venado cola blanca y otros cérvidos (Pelletier et al, 2003;Chunwang et al, 2004;McCoy & Ditchkoff, 2012;López & Montes, 2016). Esto pudo haber ocurrido por la actividad microbiana presente en las heces, las cuales metabolizan las hormonas esteroides a metabolitos con los cuales no existió reacción cruzada con los anticuerpos utilizados en este estudio.…”
Section: Season Umaunclassified
“…In the case of sex allocation in this species, the reports are scarce 16 report an efficiency of 73.75% in quantifying fecal progesterone by means of diluted extract 1:20 with cut-off value of 9000 ng/g and of 77,5% when measuring Testosterone at 1:2 dilutions, in the nonmating season with a cut-off value of 95 ng/g. However, in the mating season, in fecal progesterone diluted to 1:2 the efficiency increases to 78,75% with cut-off value of 4800 ng/g.…”
Section: Resultsmentioning
confidence: 95%
“…15 demonstrated broad individual variation in the endocrine response to stress, based on the occurrence of animals that endure more stress than others. Lopez and 16 demonstrated the effect of fecal steroid extract dilution on the estimated metabolyte levels. Additionally, the effects of the time and weathering in feces, on the sex allocation efficiency by estimation of steroidal metabolyte levels were demonstrated by.…”
Section: Resultsmentioning
confidence: 99%